Het Amsterdams Grafisch Atelier. - Martinet, Jan; Amsterdams Grafisch Atelier, Amsterdam; Gemeentemuseum Arnhem (Amsterdam : Stedelijk Museum Amsterdam, 1979)
van Alphen, Jacques ; van den Berg, Henk ; Bieruma-Oosting, Jeanne ; Blom, Theo ; Boissevain, Guus ; Bouws, Ingrid ; Bouws, Renée ; Bérénos, Etienne M. ; de Bueger, Chris ; Chaudhari, Anju ; Coumans-Schröder, Helena ; Daalder, Frank ; van der Deen, Helen ; Dieters, Coos ; Dietvorst, Netty ; van Es, Sonja ; Freymuth, Alphons ; Gaebler, Jo ; Geursen, Wilco ; de Haas, Laetitia ; Hardy, Philippe ; van der Heijden, Peter ; Hoogendijk, Wouter ; Hoogwijk, Erica ; Huismans, Sipke ; Karhof, Gea ; Kelly, Josephine ; King, David ; Kuijer, Jasper ; Kuys, Lucas ; Landsaat, Cees ; Leddy, Madeleine ; Lehousine, Malek ; Lekkerkerker, Diane ; Lodeizen, Frank ; van der Mandele, Anneke ; Mansholt, Aleid ; Peeter, Zoltin ; Reiman, Eric ; Reme, Jörg ; van Rijn, L. Joyce ; Roose, Wim ; Ruyter, Mirjam ; Sener, Mustafa ; de Staaij, Janneke van ; Staartjes, Anton ; Stolk, Joop ; de Vroom, Henk ; Wagenaar, Koosje ; Wejman, Stanislaw ; Wolfferts, Irene ; Worm, Wim ; Wout, Dick van 't ; Zuyderland, Siet
Het Amsterdams Grafisch Atelier, Stedelijk Museum Amsterdam, 15 februari - 1 april 1979, Gemeentemuseum Arnhem, 7 april - 13 mei 1979
Nederlands
boek